Experimental study on the impact of indoor air quality on creativity by Serious Brick Play method - Arikrishnan, Shmitha (2023)
Companies are increasingly asking their employees to find creative solutions to their problems. However, the office environment may reduce an employee's creative potential. In this study, the role of indoor air quality parameters (PM2.5, TVOC, and CO2) in maintaining a creative environment (involving lateral thinking ability) was evaluated by Serious Brick Play (SBP), an adaptation of the LEGO Serious Play (LSP) framework. This study was conducted in a simulated office space with 92 participants over a period of 6 weeks. The SBP required participants to address a challenge by building using Lego bricks, and then describe the solution within a given timeframe. The creations and descriptions were then graded in terms of originality, fluency, and build. The results indicated that higher TVOC levels were significantly associated with lower-rated creative solutions. A 71.9% reduction in TVOC (from 1000 ppb), improves an individual's full creative potential by 11.5%. Thus, maintaining a low TVOC level will critically enhance creativity in offices.